2010
DOI: 10.1080/00150193.2010.483381
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Fatigue of NiCr/PZT/BaPbO3Capacitors on Platinized Silicon Wafers

Abstract: BaPbO 3 and Pb (Zr 0.40 Ti 0.60 )O 3 thin films were prepared by reactive sputtering on 150 mm platinized silicon substrates. Device structures were fabricated using NiCr top electrodes. The polarization fatigue of these capacitors stacks was investigated for up to 10 9 switching cycles. Polarization decays roughly as the logarithm of the number of polarization reversals. This fatigue behavior was attributed to the NiCr top electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This suggests the potential of BaPbO 3 as a dependable conductive substrate in gamma irradiation environments. G. Suchaneek et al [ 22 ] found that both Pt/PZT/BaPbO 3 and NiCr/PZT/BaPbO 3 multilayer systems exhibited comparable patterns of fatigue, suggesting similar behavior under stress. The decline in polarization, a measure of the material's electric charge response, displayed a logarithmic connection with the frequency of polarization reversals.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the potential of BaPbO 3 as a dependable conductive substrate in gamma irradiation environments. G. Suchaneek et al [ 22 ] found that both Pt/PZT/BaPbO 3 and NiCr/PZT/BaPbO 3 multilayer systems exhibited comparable patterns of fatigue, suggesting similar behavior under stress. The decline in polarization, a measure of the material's electric charge response, displayed a logarithmic connection with the frequency of polarization reversals.…”
Section: Introductionmentioning
confidence: 99%